Research advances in the therapy of metabolic syndrome - Lin, Zitian; Sun, Luning (Frontiers in Pharmacology, 2024)
Metabolic syndrome refers to the pathological state of metabolic disorder of protein, fat, carbohydrate, and other substances in the human body. It is a syndrome composed of a group of complex metabolic disorders, whose pathogenesis includes multiple genetic and acquired entities falling under the category of insulin resistance and chronic low-grade inflammationand. It is a risk factor for increased prevalence and mortality from diabetes and cardiovascular disease. Cardiovascular diseases are the predominant cause of morbidity and mortality globally, thus it is imperative to investigate the impact of metabolic syndrome on alleviating this substantial disease burden. Despite the increasing number of scientists dedicating themselves to researching metabolic syndrome in recent decades, numerous aspects of this condition remain incompletely understood, leaving many questions unanswered. In this review, we present an epidemiological analysis of MetS, explore both traditional and novel pathogenesis, examine the pathophysiological repercussions of metabolic syndrome, summarize research advances, and elucidate the mechanisms underlying corresponding treatment approaches.